Folhas de Mangifera indica como alternativa nutricional e para o controle de Haemonchus contortus em ovinos - Kaike Magno de Macedo (2017)
The aim of this research is to evaluate the parasitological and blood parameters of experimentally infected Haemonchus contortus sheep treated with aqueous extract (EA) from mango leaves (Mangifera indica L., var. "Ubá"), as well as to evaluate the influence of leaf comminuted hay on ewe lambs before and after infection with this nematode. In the first experiment, quantitative co-cultures with seven treatments and five replicates were evaluated: levamisole phosphate (0.3 mg / g), control (distilled H 2 O) and five EA concentrations between 1.81 and 29.1 mg / g. In vivo the anthelmintic action of M. indica EA was evaluated in Santa Inês lambs, divided into two homogeneous groups containing 10 animals each, one group being treated with the EA of the mango tree at 0.601 g / kg / PC and another one not treated. Blood samples were collected for analysis of hematological and serum biochemical parameters. Blood samples were collected on days 0, 7, 14, 21 and 28 of the experiment. Efficacies between 42.5 and 88.7% were observed for inhibition of larval development, differing statistically from treatment with distilled water, and dose dependence (p <0.05) was observed. In the in vivo test the EA presented 41.8% efficacy for egg reduction in faeces after 28 days of treatment. In the second experiment the dehydrated and ground leaves of the plant were included in the diet of Santa Inês x Dorper crossbred ewes, initially treated with Albendazole to eliminate nematode infection. The animals were divided into homogeneous groups, one fed with hay from the leaves of the hose and the other not. The ewe lambs were confined in individual stalls with sand floor and received a growth diet containing 50% of bulky and 50% of concentrate. Treated ewes received shredded hay at the rate of 5 g / kg body weight (CP) to replace sorghum silage. Growth, food intake (AC) and performance were evaluated weekly and the animals were inspected for possible clinical or behavioral changes. Once a week lambs were weighed in a digital scale and food consumption was assessed and for each period the morphometric measurements were evaluated. On the 21st day of the experiment, animals from both groups were inoculated with 800 infective larvae of H. contortus / kg of PC. Leaf hay from the hose was supplied up to 35o, before the nematodes completed sexual maturity in the abomasum. For the analysis of the hematological parameters, three collections were performed in each animal for the first period (before the animals began to receive the diet containing the leaves during the adaptation period, day -14), second period (the animals were receiving the treatment and were not infected, day 7) and the third period (end of treatment and animals already infected with H. contortus, day 30). Afterwards the feces were collected on days 42, 44, 46 and 48 days for quantification of the number of eggs per gram of feces (OPG) by the Mc-Master technique. The experiment was conducted in split - plot design (two treatments x two periods) with eight replications. The averages were compared using the Scott-Knott test at 5% significance. As In the second experiment, body weight gain was lower in the second period for both groups of ewe lambs, which were infected. There was no difference in CA between the groups of animals and between the periods evaluated. In the second period, lambs infected and treated with FFM presented higher AD than the untreated group. There were no significant differences between the means of the OPG for lambs and for the evaluated days. However, there was a significant interaction of treatments and periods evaluated for eosinophil counts, which presented higher concentrations in the treated group in the last two evaluated periods. It was concluded that administration of EA mango reduces OPG infected animals after 21 days of treatment and promotes better Famacha® scores and erythrocyte, hemoglobin, hematocrit and higher -globulin concentrations relative to the control group. In addition, the use of the mashed hay of the M. indica leaves in the feeding of weaned lambs presented as a viable alternative, since it did not compromise the performance and improved the EA when the animals were infected with H. contortus.